Standardowe i specyficzne rozumienie słowa rûªḥ w tekstach Księgi Rodzaju i Księgi Wyjścia - Lemański, Janusz Adam (Verbum Vitae, 2020)
The analysis made in this article shows that the usage of the word rûaḥ in Genesis and Exodus fits with the general meanings linked to the word in other books of the Bible. In general usage this word describes, first, wind, albeit seen as 'a tool in the hand' of God used during redemptive activities to save life, life in general or that of Israel. Next rûaḥ means life, such as that present in a human being as a gift from God, which can be taken back. Finally, rûaḥ also means a charismatic strength given by God to chosen people, and that which is internal to man, his states of spirit and emotion. All of those meanings have their specificity, which is most clearly visible in so-called biblical prehistory (Gen 1:2, 3:8, 6:3, 8:1).